The World War I censorship of the Irish-American press - Mulcrone, Michael Patrick, 1948- (My University, 1993)
During World War I, editions of five Irish-American newspapers were banned from the mails by the United States Post Office. One newspaper and a magazine were forced out of business.These actions were ostensibly taken in the name of national security. This dissertation suggests, however, that the postal censorships were the culmination of a larger debate about American identity and the limits of pluralism during wartime.The dissertation examines two aspects of the press: First, how Irish-American newspapers gave voice to immigrant aspirations and helped sustain a sense of identity among the immigrant Irish and their offspring; second, how loyalty to Ireland and anger toward Great Britain produced a backlash against the Irish-American press once the U.S. entered the War.The first part of the study discusses the role of Irish-American newspapers within the national Irish-American community. The Irish-American press served as an alternative to the mainstream press. Irish-American newspapers offered an Irish interpretation of events and reinforced Irish identity, the central component of which was hatred of Britain. When the U.S. joined the War as Britain's ally, the unrelenting anglophobia of the Irish-American press came into conflict with mainstream opinion.The next section discusses role of the mainstream press in fomenting anti-Irish sentiment. The commercial daily press--with the exception of the Hearst papers--looked with suspicion upon Irish-American agitation against England. After the U.S. entered the War, the mainstream press encouraged vigilante activity and gave credence to unsubstantiated rumors of Irish/German plots. Some papers equated Irish-American nationalism with treason to the U.S.The final section examines the subsequent censorship of the Irish-American press. Postal documents reveal that officials and volunteers at the New York City Post Office were more often motivated by a desire to silence dissent than by a legitimate concern for national security. In the hysteria of the times, criticism of Great Britain and expressions of Irish-American support for national self-determination in Ireland became synonymous with disloyalty to the United States.
Thesis (Ph. D.)--University of Washington, 1993
Keywords: Theses--Communications